Relationship with Smart Phones; The Onslaught of Mass Communication - Pant, Shivani (International Journal of Control and Automation, 2018)
The goal of this research is to examine the current effects of smartphones on society and to predict how these devices will alter many facets of tomorrow's society. The goal of this research is to examine the impact of Smartphones, both for good and ill, on modern society. The effects of Smartphones on economics, teaching, medicine, and social life will be the primary areas of investigation. The research will conclude and summarise based on the many ways in which Smartphones affect modern life. The article will also include recommendations on how to lessen Smartphones' drawbacks while making the most of their many advantages.